2017
DOI: 10.1007/978-3-319-59111-7_63
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the E-Government Maturity for Public Sector Innovation in Developing Countries: Case of National Informatization Assessment Tool (NIAT)

Abstract: This paper presents a new approach to assess the e-Government maturity with an aim to facilitate public sector innovation in developing countries. NIAT takes a rare approach to comprehensively assess the needs and capabilities by a participatory measure. It provides a standardized assessment process in order to ensure the quality of data. NIAT contributes to the service innovation by providing improved contents for e-Government services and identifying priorities of ICT strategy. It also stimulates organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On the one hand, the shared spaces of constructive public discussion have created a new potential for user satisfaction aspirations and shaped mature public opinion as fueled by the knowledge exchange in operation (AL-Kaabi, 2023; Mkude & Wimmer, 2013; involving multiple stockholders, being: management, citizens, government businesses or employees (Al-Hassan et al, 2015). In parallel lines with the theoretical lens of "Public Deliberation Theory" (Habermas, 1989) and "Social Representation Theory" (Rana & Dwividei, 2017), this outcome has been among the expected advantages of governments harnessing the use of "informatisation" (Zoo et al, 2017). On the other hand, many critics have revealed that such dynamics add further pressure on the already-strained budgets of many governments worldwide at the expense of more urgent needs and causes (Greger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the shared spaces of constructive public discussion have created a new potential for user satisfaction aspirations and shaped mature public opinion as fueled by the knowledge exchange in operation (AL-Kaabi, 2023; Mkude & Wimmer, 2013; involving multiple stockholders, being: management, citizens, government businesses or employees (Al-Hassan et al, 2015). In parallel lines with the theoretical lens of "Public Deliberation Theory" (Habermas, 1989) and "Social Representation Theory" (Rana & Dwividei, 2017), this outcome has been among the expected advantages of governments harnessing the use of "informatisation" (Zoo et al, 2017). On the other hand, many critics have revealed that such dynamics add further pressure on the already-strained budgets of many governments worldwide at the expense of more urgent needs and causes (Greger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the performance of e-government is a central activity in e-government. It is important to highlight the extent of the implementation strategy and plans, ascertaining milestones accomplished, optimizing spending and identifying strengths and challenges (Zoo et al , 2017). Several authors (Alzahrani et al , 2017; Xie et al , 2017; Liu and Carter, 2018) have analysed the role of trust in the adoption of e-government services.…”
Section: Introductionmentioning
confidence: 99%